Good practice in sport science and medicine: perceptions of leaders on support and management of practitioners and teams - Alfano, H.; Collins, D.; MacPherson, A. (International Journal of Sport and Exercise Psychology, 2024)
The evaluation and delivery of good practice in the provision of Sport Science and Medicine (SSM) is clearly of interest and importance - with applied research, both anecdotal and empirical, that is burgeoning. However, no literature to date explores the role of the organisation and leader in supporting those striving to deliver good practice. The primary aim of this investigation is to explore the perceptions of experienced high-level leaders in the leadership, direction and operation of SSM practitioners and teams. A mixed methods modified Delphi technique, with three stages of investigation - a quantitative survey, individual interviews, and focus group discussions, was undertaken with 13 leaders of high-performance sport organisations in Europe and Australasia. This approach allowed expert consensus to be arrived at on a set of theoretically underpinned principles applicable to the pan regional support of good practice. A plethora of principles are offered relating to three core areas of support: organisational requirements; leadership; and practitioners´ skills and development. Importantly, a number of operational considerations for application are captured, including the impact of situational context in determining the focus and core elements of support required. Findings are particularly relevant for those leading SSM delivery - with a well led, organised and supported approach seemingly enabling good practice. In addition, results offer further empirical support to the importance of interdisciplinary teamwork, non-technical skill sets and relevant development opportunities for the practitioner. Overall, we hope the principles derived offer a practical starting point for those engaged in SSM provision.